Comparison of morphology, electrical properties and sensitivity between bulk and thin-film Mn1.5Co1Ni0.5O4 thermistors. Issue 17 (1st December 2020) - Yang, Bingwen; He, Miao; Wen, Kunhua; Xiong, Deping; Feng, Yefeng; Ta, Shiwo; Yang, Zhao
Abstract: Mn1.5 Co1 Ni0.5 O4 (MCN) bulk sensors and ceramic targets were prepared via the solid-state reaction method. MCN functional thin-film and Au electrode thin-film layers were fabricated on polished alumina substrates by employing a series of semiconductor processes; these involved physical vapour deposition, photolithography, and wet etching. The X-ray diffraction (XRD) patterns of the MCN thin film exhibit MCN spinel-structure peaks on the alumina substrate. Negative temperature coefficient temperature and resistance relationships of the bulk and thin-film thermistors were elucidated by measuring the resistance of thermistors in thermostatic oil both the resistance of the bulk sensor at 25 °C was measured to be 2077 Ω, while the thin-film sensor recorded resistance values exceeding 300 kΩ. The activation energy and B value of the thin-film sensor were slightly lower than those for the bulk sensors. The thermal response time constant of the bulk sensor was 5.13 s; meanwhile, for the thin film sensors, the time constants were 0.43 s, 0.46 s and 0.53 s, corresponding to the thicknesses of 528, 610 and 677 nm, respectively.